A touch screen monitor application for cashier [electronic resource] - Liew, Hon Chin, 1988- , author; Musa Mohd. Mokji, supervisor (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2011